Asuhan Keperawatan Gerontik pada pasien dengan Osteoarthritis di Panti Sosial Tresna Werdha Sabai Nan Aluih Sicincin Kabupaten Padang Pariaman - Azizah .; Sandra Dewi; Kheniva Diah Anggita; Armaita . (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
Osteoarthritis is a degenerative joint disease caused by damage and thinning of the cartilage that protects the ends of bones, resulting in friction between bones and causing pain, stiffness, and swelling, especially in the knees, hips, spine, and fingers. Globally, approximately 528 million people live with osteoarthritis. In Indonesia, the prevalence of osteoarthritis reaches 15.5% in men and 12.7% in women. In West Sumatra, the prevalence reaches 12.7%, with the highest rates found in Pesisir Selatan and Padang Pariaman Regencies. Based on data from the Sabai Nan Aluih Sicincin Social Home for the Elderly in Padang Pariaman Regency, there were seven elderly individuals diagnosed with osteoarthritis. This study aimed to provide geriatric nursing care for patients with osteoarthritis. The research method used was a case study conducted on one managed client from February 11–16, 2026 through observation, interviews, physical examinations, and documentation studies. The results identified nursing problems including chronic pain, impaired physical mobility, and self-care deficits. Interventions provided included pain management, mobilization support, and self-care support. After five days of implementation, the client’s condition improved as indicated by reduced pain levels, increased physical mobility, and improved self-care ability although partial assistance was still needed. It is expected that elderly patients with osteoarthritis will continue independent care practices such as warm compresses, deep breathing techniques, light massage, and range of motion (ROM) exercises.